Implementasi Kebijakan Penanganan Covid-19 di Desa Wilayah Kecamatan Selakau Kabupaten Sambas Kalimantan Barat - Rusdiono Rusdiono; Pardi Pardi (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2022)
This research is motivated by the existence of a policy issued by the government, namely Permendes No. 6 of 2020 concerning Priority for the Use of Village Funds. This study aims to determine the factors that affect the success of handling Covid-19 in Selakau District. This type of research is qualitative research. The results showed that 1) Communication and coordination between implementing actors was carried out well, namely an understanding of the tasks carried out between agencies in handling Covid-19 which resulted in extraordinary synergy in the success of handling Covid-19. 2) The attitude of the implementers shown by the actors / implementers in handling Covid-19 was very good in responding to various policies set by the government. With the attitude of the implementers, it gives public confidence in the implementation of the Covid-19 prevention policy. 3). Human resource support was demonstrated by the formation of Task Force Teams at the Village and Subdistrict Levels. In terms of financial resources, the government has issued various regulations to be able to support the success of this program including Permendes No. 11 of 2019 concerning Priority for the Use of Village Funds which provides opportunities for village governments to use Village Funds for BLT in handling Covid-19 4) The bureaucratic structure implemented in handling covid-19 takes an open bureaucratic structure model, meaning that this model provides opportunities wide for all parties to be involved in the formulation of goals and there is space in forming new institutions, new models or strategies that are more locally oriented, such as developing a solution system a problem based on the participation of all elements, so that there are wider opportunities for involvement bottom-up and top-down balanced. Keywords: Implementation, Policy, Village Fund BLT, Covid-19